Regulation patterns in signaling networks of cancer - Schramm, Gunnar; Nandakumar, Kannabiran; König, Rainer (BMC systems biology, 2010)
Formation of cellular malignancy results from the disruption of fine tuned signaling homeostasis for proliferation, accompanied by mal-functional signals for differentiation, cell cycle and apoptosis. We wanted to observe central signaling characteristics on a global view of malignant cells which have evolved to selfishness and independence in comparison to their non-malignant counterparts that fulfill well defined tasks in their sample.